2015
DOI: 10.1149/2.0041509eel
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Li Deposition by Glow Discharge Optical Emission Spectroscopy in Post-Mortem Analysis

Abstract: Glow discharge optical emission spectroscopy (GD-OES) is employed to detect and quantify Li deposition as a function of depth on graphite electrodes. Commercial cells with graphite anodes were subject to Li plating by being cycled at 5 Li-ion batteries suffer from aging reactions which limit their lifetime in applications.1,2 It is known that chemical reactions such as SEI growth on anodes and dissolution of cathode active material are accelerated with increasing temperature, following an Arrhenius-like behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 22 publications
11
56
0
Order By: Relevance
“…This indicateda ni nhomogeneous phase distribution over the electrode depth because the ratio between LiC 6 and LiC 12 was stronger.F rom simulations, more of the LiC 6 wase xpected to be located at the anode surface( near the separator). [45] This was in accordance with measurements [20,33,42,46] and simulations [17] that have shown that Li deposition (favored by high lithiationd egrees) [18,47] is also mostly located on the anode surface.…”
Section: Effects Of Temperaturea Nd Aging On the Intercalationmechanisupporting
confidence: 89%
“…This indicateda ni nhomogeneous phase distribution over the electrode depth because the ratio between LiC 6 and LiC 12 was stronger.F rom simulations, more of the LiC 6 wase xpected to be located at the anode surface( near the separator). [45] This was in accordance with measurements [20,33,42,46] and simulations [17] that have shown that Li deposition (favored by high lithiationd egrees) [18,47] is also mostly located on the anode surface.…”
Section: Effects Of Temperaturea Nd Aging On the Intercalationmechanisupporting
confidence: 89%
“…47,48 Indeed, an estimation based on the Li and O depth profile 47 revealed that Li metal is present in this sample. This fits to the optical appearance of the anode which is shiny and metallic (see inset of Figure 4c).…”
Section: Post-mortem Analysis Reveals Different Aging Mechanisms In 325mentioning
confidence: 81%
“…13 Clear trends were observable for E anode vs. (Li/Li + ) in Figure 4 for all three tested temperatures. In particular, the following tendencies were found: These findings regarding low temperatures, high charging C-rate, and high SOC are discussed in the following using Figures 5a-5c, respectively.…”
mentioning
confidence: 83%